EFFECT OF HEATED CANOLA OIL ON AORTA WALL THICKNESS IN RATS - Aziz, Mochammad Abdul; I'tishom, Reny; Rejeki, Purwo Sri; Yuliawati, Tri Hartini (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlights: 1. The use of re-heated cooking oil can give negative impact on health, especially on the cardiovascular system. 2. Unlike other types of cooking oil, repeated heating of canola oil did not show significant change in aortic wall thickness. Abstract Background: Structural alteration of blood vessels such as formation of atheroma or changes in the thickness of vessel walls, are heavily involved in pathogenesis of cardiovascular disease. Several studies have shown that canola oil has a positive effect on such diseases by reducing LDL and cholesterol levels. However, there may be several negative impacts on reheating canola oil upon administration, similar to other oils. Although canola oil can improve lipid profiles, studies related to how canola oil alters the structure of blood vessels are limited. Objective: The aim of this study was to investigate the effect of heated canola oil on intimal-to-medial thickness (IMT) of Thoracic aorta in high-fat diet rats. Material and Method: A total of 27 rats were divided into 3 groups, the K+, P1, and P2. Rats among the three groups were given a high-fat diet for 14 days, accompanied by consumption of canola oil without heating in the P1, and with repeated heating in the P2. Thoracic aorta was taken on the 15th day and then processed into histological preparations. IMT was measured using CellSens software on a microscope with a magnification of 400. The difference between groups was tested using the one-way ANOVA test on SPSS. Result: The mean and standard deviations of each group in a row were K+ (134.96 and 21.27) P1(132.04 and 27.30) and P2 (152.05 and 31.75). There was no significant difference in IMT between groups (p >0.05). However, the P2 group showed the highest mean of IMT. Conclusion: The consumption of canola oil with or without repeated heating did not result in the changes of the IMT in rats fed with a high-fat diet.